2014
DOI: 10.1002/j.2161-0045.2014.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

A Moderated Mediation Model of Planned Happenstance Skills, Career Engagement, Career Decision Self‐Efficacy, and Career Decision Certainty

Abstract: This study examined how college students’ levels of planned happenstance skills influenced the relationships among career engagement, career decision self‐efficacy, and career decision certainty. Moderated mediation analysis was used with a sample of 217 Korean undergraduate students. The results indicated that career decision self‐efficacy mediated the relationship between career engagement and career decision certainty. Moreover, the positive indirect effect of career engagement on career decision through ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 31 publications
(44 reference statements)
9
56
1
9
Order By: Relevance
“…Using planned happenstance theory (Mitchell et al, 1999), B. Kim, Jang, et al (2014) developed and initially validated the Planned Happenstance Career Inventory (PHCI) to measure how responses to unexpected opportunities could influence career choice. In the initial scale development process, they conducted exploratory and confirmatory factor analyses (CFAs) to verify the inventory’s five‐factor structure and provided support for its construct validity, internal consistency, and reliability.…”
Section: Planned Happenstance Theory and Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…Using planned happenstance theory (Mitchell et al, 1999), B. Kim, Jang, et al (2014) developed and initially validated the Planned Happenstance Career Inventory (PHCI) to measure how responses to unexpected opportunities could influence career choice. In the initial scale development process, they conducted exploratory and confirmatory factor analyses (CFAs) to verify the inventory’s five‐factor structure and provided support for its construct validity, internal consistency, and reliability.…”
Section: Planned Happenstance Theory and Measurementmentioning
confidence: 99%
“…Additional research revealed that the PHCI had a positive relationship with career engagement and career self‐efficacy (B. Kim, Jung, et al, 2014). PHCI skills were also related to career satisfaction (B. Kim, Rhee, Ha, Yang, & Lee, 2016).…”
Section: Planned Happenstance Theory and Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…At first, Mitchell et al (1999) brought out five yin type of planned happenstance skills: Curiosity refers to exploring new learning, persistence to exerting efforts in spite of setbacks, flexibility to adjusting to change, optimism to believing in new opportunities, and risk-taking to taking action in spite of uncertainty. Positive relationship between these skills and career evolution has been found (e.g., Magnuson et al, 2003; Kim et al, 2014). …”
Section: Theoretical Foundationmentioning
confidence: 99%